Influence of Spacing and Mulching on Strawberry (Fragaria x ananassa Duch.) cv. Sweet Charlie in Assam - Himadri S. Datta; P.C. Barua; U. Kotoky; R. Das; H. Saikia; H.K. Devanath; Binita Hazarika (Archives of Current Research International, 2025)
Plant spacing and mulching material have effects on crop growth and yield as they play a vital role in conserving soil moisture, enhancing nutrient and moisture uptake, regulating soil temperature and reducing weed growth. Evident research gap exists on effects of spacing and mulching on growth and development of strawberry. Strawberry is a surface feeder crop, and hence, mulching plays a very important role in providing optimum conditions for root development. Therefore, a field experiment was conducted at the farmer’s field in Jorhat district of Assam, during 2019-20 and 2020-21 to study the effect of plant spacing and mulching on root volume of strawberry cv. Sweet Charlie. The experiment was laid out in a randomized block design with three replications based on 2 factors viz. plant spacing and mulch material. The trial consisted of a total of twenty treatments keeping five different plant spacing levels viz., 20 cm × 30 cm (S1), 30 cm × 30 cm (S2), 30 cm × 40 cm (S3), 40 cm × 40 cm (S4), 40 cm × 60 cm (S5) and four different mulching materials viz., paddy straw (M1), red mulch (M2), silver black mulch (M3) and no mulch (M4). Results revealed that 40 cm × 60 cm spacing under silver black mulch recorded maximum root volume which may have a positive impact on crop yield.